Probabilistic available transfer capability calculation considering static security constraints and uncertainties of electricity–gas integrated energy systems. (1st April 2016) - Wei, Zhinong; Chen, Sheng; Sun, Guoqiang; Wang, Dan; Sun, Yonghui; Zang, Haixiang
Highlights: ATC considering the static security constraints of both EPSs and NGSs is proposed. The LPC method is formulated to calculate ATC in a fast and accurate way. The uncertainties of IESs are addressed by a combination of LHS and the Nataf transformation. The corrective adjustment in NGSs can increase the ATC efficiently. Abstract: The increasing share of natural gas-fired power plants (NGFPPs) has strengthened the linkage between electric power systems (EPSs) and natural gas systems (NGSs). It is imperative to analyze both systems jointly. In this paper, a probabilistic available transfer capability (PATC) model considering the static security constraints and uncertainties of electricity–gas integrated energy systems (IESs) is proposed. The concept of IES steady-state security regions is developed, and the mathematical model of ATC within IES security regions is formulated. The active constraint limiting the ATC is identified by the linear prediction and calculation (LPC) method, and then it is augmented into IES energy flow equations to determine the value of ATC. The uncertainties of correlated electricity/gas loads and wind power generations are also taken into account and are addressed by a combination of Latin hypercube sampling (LHS) and the Nataf transformation. Moreover, the corrective adjustment in NGSs can be adopted to ensure the fuel availability of NGFPPs. Finally, test results on the modified IEEE 118-bus system and a 20-node NGS are presented to verify the applicability of the proposed methodology.